Influence of gender and quality of sleep in cognitive impairment: A cross-sectional pilot study from Kerala, India - Rajeev, Akhil; Nair, Bindu P. (Journal of Biomedical Sciences, 2023)
Background: Cognitive decline, a natural aging process, can lead to geriatric neurodegenerative diseases like dementia, which progresses rapidly, with memory complaints and deficits being particularly risky. Sleep is crucial for psychological functions and cognitive functions. The aim of this study was to investigate the connection between the sleep quality and cognitive function like working memory, reaction time (simple and choice reaction time), and attention (sustained/vigilant attention and divided attention) in the south Indian youth population.Material and methods: A cross-sectional pilot study was carried out on the 30 participants. Pittsburgh Sleep Quality Index (PSQI) was used to assess the sleep quality, NIMHANS Neuropsychological Battery for adults was used to assess different neuro-cognitive domains and Computerized test of reaction time to assess the simple reaction time and choice reaction time.Results: Participants with poor sleep quality showed impaired performance in the tests of attention (Sustained attention and Divided attention). No significant differences were observed between participants of good sleep quality and poor sleep quality in the test of working memory, N Back 1 test (t=0.539, p>0.05) and N Back 2 test of working memory (t=0.306, p>0.05).ConclusionL Participants with poor sleep quality significantly differed from those with good sleep quality and committed more mistakes in the triad test of divided attention, spend longer time, and committed errors in the completion of the digit vigilance test of sustained attention. Sleep patterns are associated with cognitive test performance, and optimising sleep duration and quality should be an important consideration for cognitive functions.